Acquired Resistance to Antiangiogenic Therapies in Hepatocellular Carcinoma Is Mediated by Yes‐Associated Protein 1 Activation and Transient Expansion of Stem‐Like Cancer Cells. Issue 5 (24th November 2021) - Castven, Darko; Czauderna, Carolin; Becker, Diana; Pereira, Sharon; Schmitt, Jennifer; Weinmann, Arndt; Shah, Viral; Hajduk, Jovana; Keggenhoff, Friederike; Binder, Harald; Keck, Tobias; Heilmann‐Heimbach, Stefanie; et al.
Abstract : Induction of neoangiogenesis is a hallmark feature during disease progression of hepatocellular carcinoma (HCC). Antiangiogenetic compounds represent a mainstay of therapeutic approaches; however, development of chemoresistance is observed in the majority of patients. Recent findings suggest that tumor‐initiating cells (TICs) may play a key role in acquisition of resistance, but the exact relevance for HCC in this process remains to be defined. Primary and established hepatoma cell lines were exposed to long‐term sorafenib treatment to model acquisition of resistance. Treatment effects on TICs were estimated by sphere‐forming capacity  in vitro, tumorigenicity in vivo, and flow cytometry. Adaptive molecular changes were assessed by whole transcriptome analyses. Compensatory mechanisms of resistance were identified and directly evaluated. Sustained antiproliferative effect following sorafenib treatment was observed in three of six HCC cell lines and was followed by rapid regrowth, thereby mimicking responses observed in patients. Resistant cells showed induction in sphere forming in vitro and tumor‐initiating capacity in vivo as well as increased number of side population and epithelial cell adhesion molecule‐positive cells. Conversely, sensitive cell lines showed consistent reduction of TIC properties. Gene sets associated with resistance and poor prognosis, including Hippo/yes‐associated protein (YAP), were identified. Western blot and immunohistochemistry confirmed increased levels of YAP. Combined treatment of sorafenib and specific YAP inhibitor consistently revealed synergistic antioncogenic effects in resistant cell lines. Conclusion: Resistance to antiangiogenic therapy might be driven by transient expansion of TICs and activation of compensatory pro‐oncogenic signaling pathways, including YAP. Specific targeting of TICs might be an effective therapeutic strategy to overcome resistance in HCC.